Managing a World Heritage Site in the Face of Climate Change: A Case Study of the Wet Tropics in Northern Queensland - Weber, Ellen T.; Catterall, Carla P.; Locke, John; Ota, Liz S.; Prideaux, Bruce; Shirreffs, Leslie; Talbot, Leah; Gordon, Iain J. (Earth (Basel, Switzerland), 2021)
World Heritage is the pinnacle of the recognition of the natural, aesthetic, and cultural value of a place on the planet. Since its inception in 1972, over 1100 sites have received World Heritage status. Many of these places are being challenged by the effects of climate change. Urgent action is needed to build the resilience and adaptive capacity of World Heritage sites in the face of climate change threats to come. The Wet Tropics of Queensland World Heritage Area (WTWHA) is one of the most effectively regulated and managed protected Areas in the world. This includes the scientific evidence upon which that regulation and management is based. However, there is growing evidence that climate change impacts are a clear and present threat to the Outstanding Universal Value (OUV) upon which the listing is based. This challenges the very concept of OUV and points to the business-as-usual regulation and management not being sufficient to deal with the threat. It also calls for quantum changes in the approaches to protecting natural and cultural heritage and the OUV in World Heritage Areas. This WTWHA case study gives insights into the journey travelled and the pathways that need to be laid out to protect our most cherished internationally recognised natural and cultural landscapes. We demonstrate the importance of evidence in support of advocacy and management action to address the clear impacts of climate change on species, ecosystems, people, and societies living in the WTWHA. The strategic and climate adaptation plans provide the framework upon which these actions take place. Community engagement in the delivery of mitigation, adaptation, and resilience policy is key to the long-term future of the WTWHA.